Mapeamento geoambiental da bacia do arroio Inhacundá, São Francisco de Assis/RS - Sangoi, Dionisio Saccol (2006)
The Inhacundá River Basin Area which comprended between the coordinates 54° 59 32 e 55°20 10 West and 29°20 00 e 29°37 23 South. with area of the 36.333,74 hectares. This Basin is situated into the limits of municipality of the São Francisco de Assis, located in Campanha Region; southwest of the Rio Grande do Sul State. The objective of this work was mapping geoenvironmetal units with helpened by: Morphometrical Parameters, Spatial Occupations; Geological studies and. Surfaces Structures. The methodological approach consisted in crossing four different maps: Geological, Land Units, Spatial Occupations and Surfaces Structures. The Results funded showing that basin presents Seven Geoenvironmetal Units. With special attention to Two units located in lower Inhacundá, which presents problems with gully erosion and sandification. The Use of the Geoenvironmetal Mapping is correct because permitted realized a correct evaluation of the area, proposed to discuss about potentialities of this basin.